CITY BRANDING SAIL TO INDONESIA 2019 DI PULAU BAWEAN SEBAGAI UPAYA MENINGKATKAN KUNJUNGAN WISATAWAN - Reza Arfiyan; Anam Miftakhul Huda (SOURCE : Jurnal Ilmu Komunikasi, 2020)
Sail to Indonesia 2019 in Bawean Island is a program implemented by the Indonesian Ministry of Tourism in collaboration with yacht rally organizer from New Zealand. Sail to Indonesia has the purpose  to develop tourism sector, especially maritime tourism in the area that is the path and center of Sail to Indonesia.  Sail to Indonesia 2019, Yachters sailed in 10 places in Indonesia for three months, one of that in Bawean Island and Bawean Island became the only place in East Java which was visited by the Yachters. This research uses descriptive qualitative method that aims to analyze and determine the formation of the Sail to Indonesia 2019 image on Bawean Island as an effort to increase tourist visits. The results of this study concluded that the Department of Tourism & Culture of Gresik in forming the image of Bawean Island not only applied the theory of uniqueness of events according to Getz such as hospitality, symboliysm, authenticity, theming, and festive spirit, but also there is an element of convenience. Department of Tourism & Culture of Gresik did efforts to increasing tourist visits are by using wish images to maximize expectations of Bawean Island so as to provide the best service during activities. In addition, through the current image, tourists will tell all their best experiences and memories while on Bawean Island with word of mouth marketing.